Analyzing Equivalency and Accuracy of Three Different Periodontal Probes in Measuring Pocket Depth - An In-Vitro Study - Rachel Koh; Sharon Lee; Udochukwu Oyoyo; So Ran Kwon; Nima D. Sarmast (Taylor & Francis Group, 2023)
ABSTRACTBackground The periodontal probe is an essential instrument designed for the purposes of recording clinical periodontal data. As such, accurate periodontal measurements remain a critical factor in providing individualized care to patients. The purpose of this study is to determine the compatibility and accuracy of three different periodontal probes on a periodontal typodont model.Materials and Methods Forty-one D3, D4, and DH students were randomly selected to perform a 6-point pocket depth measurement on the mandibular teeth of a previously verified periodontal typodont mounted on a manikin. Each measurement site was outlined with black marking on the tooth to facilitate consistent reproducibility in periodontal probe placement and angulation.Results Probing depth measurements between the UNC-15, PCP-126, and Disposable i-PAK® periodontal probe rendered an excellent equivalency (ICC = 0.960) with narrow CI (0.947, 0.971). There is significant difference among these three instruments in their capability to replicate the manufacturer's suggested probing depth on the periodontal typodont (p < .001). The UNC-15 probe was the most accurate, followed by PCP-126, with the Disposable i-PAK® being the least accurate.Conclusions This study demonstrated that the UNC-15, PCP-126, and Disposable i-PAK® yielded equivalent results when measuring probing depths on a periodontal typodont. Furthermore, the UNC-15 was most accurate in its ability to replicate the manufacturer's suggested pocket depth on the periodontal typodont.Practical Implications This study emphasizes the importance in consistency of periodontal probe types in the dental practice.